2013
DOI: 10.1021/es3033555
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Bioremediation of Uranium with Emulsified Vegetable Oil as the Electron Donor

Abstract: A field test with a one-time emulsified vegetable oil (EVO) injection was conducted to assess the capacity of EVO to sustain uranium bioreduction in a high-permeability gravel layer with groundwater concentrations of (mM) U, 0.0055; Ca, 2.98; NO3(-), 0.11; HCO3(-), 5.07; and SO4(2-), 1.23. Comparison of bromide and EVO migration and distribution indicated that a majority of the injected EVO was retained in the subsurface from the injection wells to 50 m downgradient. Nitrate, uranium, and sulfate were sequenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 43 publications
0
70
0
Order By: Relevance
“…Therefore, the range of hydraulic conductivity reported in this study was notably less (up to two orders of magnitude) than to the value previously reported. It is important to note that Watson et al (2013), and Phillips et al (2008), also reported that the fill material was gravelly, whereas no gravel component is known to exist within the area of this study site. Therefore, the lack of a gravel component in the fill material within the study site may explain the lower values of hydraulic conductivity.…”
Section: Discussion: Hydraulic Conductivitymentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, the range of hydraulic conductivity reported in this study was notably less (up to two orders of magnitude) than to the value previously reported. It is important to note that Watson et al (2013), and Phillips et al (2008), also reported that the fill material was gravelly, whereas no gravel component is known to exist within the area of this study site. Therefore, the lack of a gravel component in the fill material within the study site may explain the lower values of hydraulic conductivity.…”
Section: Discussion: Hydraulic Conductivitymentioning
confidence: 77%
“…However, Watson et al (2013) reported that the hydraulic conductivity of the fill material, in Area 2 test wells immediately east of the study site, was approximately Table 3 Effective porosity calculated from the truncated and expanded solutions, (20) and (18), respectively, for tests in this study (FW220-FW225) and for tests from Hall et al (1991) and Istok (2013) …”
Section: Discussion: Hydraulic Conductivitymentioning
confidence: 86%
“…Baker). Linear combinations of these three standard spectra accounted for >99% of the measured counts indicating no 8 significant content of other γ-emitting radionuclides in these soils. Results were expressed as mass of each element per unit weight of air-dried soil (i.e., µg g -1 ) to be directly comparable with other analytical methods.…”
Section: Core Materials Geochemical Analysismentioning
confidence: 97%
“…A large mixed waste plume of contaminated groundwater is preferentially migrating away from the ponds towards nearby Bear Creek [5][6][7][8]. Rates and mechanisms of immobilization and natural attenuation of metals, radionuclides (i.e., U, Th) and co-contaminants like nitrate are being studied at the U.S. DOE Oak Ridge Integrated Field Research Challenge (ORIFRC) field site located near the S-3 ponds [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In situ bioremediation processes have been demonstrated in the field for metal(loid)-contaminated groundwater (including uranium) using both iron-reducing bacteria (e.g., Anderson et al, 2003) and sulfate-reducing bacteria (Saunders et al, , 2008Tang et al, 2013;Watson et al, 2013;Wu et al, 2006). Taken together, these approaches are apparently analogous in real time to the important redox geochemical and geomicrobiologic processes that were involved in the formation of roll-front uranium ores.…”
Section: Redox and The Formation Of Roll-front Depositsmentioning
confidence: 99%